2022
DOI: 10.33963/kp.a2021.0132
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of coronary sinus reducer implantation in patients with chronic total occlusion of the right coronary artery

Abstract: Background: Clinical efficacy of coronary sinus reducer (CSR) in refractory angina (RA) patients with ischemia due to the chronic total occlusion (CTO) of the right coronary artery (RCA) remains unknown. Aims:To evaluate the efficacy of CSR implantation in RA patients with CTO RCA and compare them to CSR recipients with left coronary artery (LCA) ischemia.Methods: Consecutive patients with CTO RCA from 2 centers were prospectively included and compared to patients with LCA ischemia. All patients underwent eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…All patients were discharged on the following day after the implantation procedure. Similar to our findings, recently published data confirmed the safety and efficacy of the procedure [7][8][9][10][11]. Nevertheless, we observed a slightly higher success rate in comparison to other studies.…”
Section: Resultssupporting
confidence: 92%
“…All patients were discharged on the following day after the implantation procedure. Similar to our findings, recently published data confirmed the safety and efficacy of the procedure [7][8][9][10][11]. Nevertheless, we observed a slightly higher success rate in comparison to other studies.…”
Section: Resultssupporting
confidence: 92%
“…The characteristics of the included studies are presented in Table 1 (Ref. [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]). Twelve studies with a total of 1679 patients undergoing CSR implantation were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies were randomized and blinded with a sham procedure. Some non-randomized studies also showed the improvement of left ventricular perfusion by SPECT or magnetic resonance imaging [ 14 , 15 , 16 , 17 ]. However, potential antiarrhythmic effects were not assessed.…”
Section: Discussionmentioning
confidence: 99%